Pasture Stocking Density and the Relationship to Animal Performance - Matt Hersom (EDIS, 2005)
The pasture/livestock production enterprise should be viewed as an integrated production system. An important step in improving the production efficiency of the system is to consider the interrelationship between the cattle and the pasture forage supply. Management of stocking density is one such relationship between grazing cattle and pastures. The stocking density of Florida pastures can impact beef cattle production, forage production, and enterprise profitability. The overall goal of managing grazing animals is to utilize the forage that a pasture already produces to its optimum potential. This document is AN155, one of a series of the Department of Animal Sciences, UF/IFAS Extension. Original publication date August 2005.